Patient-Centered Outcomes in an Interdisciplinary Clinic for Complex Children with Autism. Issue 3 (April 2021) - Suen, Catherine G.; Campbell, Kathleen; Stoddard, Gregory; Carbone, Paul S.
ABSTRACT: Objective: To compare the perspectives of caregivers of children with autism receiving care at the Neurobehavior Healthy Outcomes Medical Excellence (HOME) Program, an interdisciplinary clinic that provides primary care and behavioral/mental health services for patients with autism and other developmental disabilities, with those responding to the 2016 National Survey of Children's Health (NSCH). We focused on ratings related to shared decision-making, care coordination, family-centered care, and care within a medical home. Methods: We administered a subset of items from the 2016 NSCH to caregivers of children with autism enrolled in HOME and compared responses with the same items from a nationally representative group of caregivers of children with autism who completed the 2016 NSCH. We compared the proportions that reported receiving shared decision-making, care coordination, family-centered care, care within a medical home, and unmet needs among the 2 study groups using Poisson regression, controlling for age, sex, race/ethnicity, payor, autism severity, and intellectual disability (ID). Results: Compared with the NSCH cohort (n = 1151), children enrolled in HOME (n = 129) were older, more often female, had severe autism, and had co-occurring ID. Caregivers perceived that children receiving care within HOME more often received family-centered, coordinated care within a medical home compared with a national sample of children with autism. HOME enrollees also reported increased access to behavioral treatments and adult transition services with less financial burden compared with the national sample. Conclusion: An interdisciplinary clinic model may best serve children with autism, especially those with higher severity symptoms and co-occurring conditions.